THE IMPLICATION OF TEACHING METHOD AND STUDENT’S SCHEMA THROUGH READING COMPREHENSION ON FACING ASEAN ECONOMIC COMMUNITY - Irpan Ali Rahman (Proceedings Education and Language International Conference, 2017)
The purpose of the research is to know the effect of teaching method, student’s schema through reading comprehension on facing of Asean Economic Community. To collect the data, the writer persuade two techniques on teaching English, they are conventional and contextual technique. The method used in this research is quantitative research by using a survey method and correlation technique. The method and the technique have intention to know the correlation among dependent variable (Y), it is Reading comprehension while teaching method (A), and Student’s Schema (B) as the two of independent variables. The characteristics of the descriptive method are to give the existence of the data, straight to the problems and the recent variables aren’t manipulated by the writer. Furthermore, the writer got the data by giving short and simple of reading comprehension exercise to the participants. The writer got some findings about the effect of teaching method and student’s schema through reading comprehension. Based on the teaching method by using SQ3R found that Fh = 18.683 that is higher than Ft = 3,15 and the student’s schema is Fh = 38.163, that is also higher than Ft = 3,15. So, the result of reading comprehension score through contextual method (SQ3RR) and student’s schema have high significant score than conventional method. Finally, we may say that there is the different effect between contextual method and conventional method. Keywords: Teaching technique, SQ3R, Student’s schema, Reading Comprehension